The use of penile traction therapy in the management of Peyronie's disease: current evidence and future prospects. (March 2019) - Valenzuela, Robert; Ziegelmann, Matthew; Tokar, Sam; Hillelsohn, Joel
Peyronie's disease is a disorder of abnormal and dysregulated wound healing leading to scar formation in the tunica albuginea of the penis. Penile traction therapy has emerged as an attractive therapeutic option for men with Peyronie's disease in both the acute and chronic phases. Currently, clinical studies are limited by lack of randomization, small cohorts, and lack of patient compliance with therapy. Despite these shortcomings, studies have shown a potential benefit with minimal morbidity. Specifically, penile traction may help to preserve or increase penile length and reduce penile curvature when used as monotherapy or as adjuvant therapy for surgical and intralesional treatments. Further study is necessary to define patient characteristics that are predictive of improved outcomes, determine the duration of treatment needed for clinical effect, and improve patient compliance.